2007
DOI: 10.1016/s1001-0742(07)60080-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of anthropogenic influences on water quality of rivers in Taihu watershed

Abstract: Surface water bodies are progressively subjected to stress as a result of anthropogenic activities. This study assessed and examined the impact of human activities on spatial variation in the water quality of 19 rivers in the Taihu watershed. Concentrations of physicochemical parameters of surface water quality were determined at the mouth of each river during the period of 2000-2004. Multivariate statistical techniques were applied to identify characteristics of the water quality in the studied rivers. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(78 citation statements)
references
References 16 publications
4
70
0
4
Order By: Relevance
“…As stated above, the concentrations of TP showed significant seasonal and spatial variation (p < 0.001) and TP levels were comparatively high for most of the locations in winter 2015. Wang et al [27] reported similar TP levels for rivers surrounding Taihu Lake. Possible runoff from fertilized lawns and cropland, animal manure, and also domestic sewage entry into the water are likely causes [47].…”
Section: Physico-chemical and Microbiological Parametersmentioning
confidence: 76%
“…As stated above, the concentrations of TP showed significant seasonal and spatial variation (p < 0.001) and TP levels were comparatively high for most of the locations in winter 2015. Wang et al [27] reported similar TP levels for rivers surrounding Taihu Lake. Possible runoff from fertilized lawns and cropland, animal manure, and also domestic sewage entry into the water are likely causes [47].…”
Section: Physico-chemical and Microbiological Parametersmentioning
confidence: 76%
“…Nutrient variables and V-phen contributed the greatest variance of total variation of water quality, which presented the dominant environmental problems to the Canal. Considering that V-phen mainly came from sewage of organicchemistry industry, high consistency in variations of nutrients and V-phen suggested urbanization and industry played a dominant role in variation of water quality within the Canal, although Cao et al (2004) and Wang et al (2004) argued that runoff from agricultural contributed more than 60% nutrients loss in Taihu Region. Only Petro significantly related to factor 3 (counting for 13.5% of the total variance of water quality), which indicated that shipping is an important pollutant resource to the Canal, in view that Petroleum in rivers of Taihu watershed mainly leaked from watercrafts (Cai et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The sampling sites were close to areas of human habitation, agricultural land and forest land [68]. In order to quantify the NO 3 − -N sources in the rivers, it was assumed that the nitrate of the rivers mainly comes from three sources (chemical fertilizer, soil organic N, and sewage) because of the type of land use around the rivers.…”
Section: Quantification Of Nitrate Sources In Riversmentioning
confidence: 99%